Evaluating Deviant Art as an Educational Tool for Collaborative Learning - Christoforou, Maria (My University, 2020)
The widespread use of technology has reshaped the field of language teaching and has transformed the learning experience for language learners. The implementation of multimedia tools has nurtured opportunities for more student-centred, real-world-like learning environments where students can become more autonomous and collaborate with their peers. Pedagogically, the collaborative nature of these tools is founded under the social constructivist theory according to which learning takes place through social interactions and language use, and knowledge is shared and becomes more meaningful. The multimedia tool involved in the present study is Deviant Art, an international online community for art enthusiasts, featuring artwork, photography and videography. Within this social community, artists can connect through their art, share their work, engage in constructive feedback and keep their own journal about their work. The present pilot study focuses on the evaluation of Deviant Art as an educational tool, as it was used in the course English for Specific Academic Purposes (ESAP) in the Fall Semester of 2019, at the Cyprus University of Technology (CUT). The evaluation was based on the experience of 11 first-year students of the Department of Fine Arts. The aim of the paper was to investigate students’ perceptions on Deviant Art as an educational tool for creating collaborative learning opportunities and to examine up to what extent they intended to continue with the Social Networking (SN) tool after the termination of the course. Data was collected through the students’ reflection journals, the instructor’s field notes and through an online questionnaire, submitted at the end of the semester.
Keywords: Deviant Art; ICT; Collaborative learning; ESAP; Higher Education